Comics Squad. Detention! - Holm, Jennifer L; Holm, Matthew; Krosoczka, Jarrett; Krosoczka, Jarrett; OConnor, George; Jamieson, Victoria; Hatke, Ben; Rosado, Rafael (Animator); Pien, Lark; Phelan, Matt; Holm, Jennifer L. (Comics squad., 2017)
An anthology of comics by well-known graphic novelists on the theme of detention.